Protocol for the Exercise, Cancer and Cognition – The ECCO-Study: A Randomized Controlled Trial of Simultaneous Exercise During Neo-/Adjuvant Chemotherapy in Breast Cancer Patients and Its Effects on Neurocognition - Kiesl, David; Kuzdas-Sallaberger, Marina; Fuchs, David; Brunner, Silvana; Kommenda, Romana; Tischler, Clemens; Hornich, Herwig; Akbari, Kaveh; Kellermair, Jörg; Blessberger, Hermann; Ocenasek, Helmuth; Hofmann, Peter; et al. (Frontiers in Neurology, 2022)
Introduction: Epidemiological research indicates that increased levels of physical activity are associated with decreased breast cancer risk and mortality. Thereby, exercise programs can substantially increase patients` quality of life during and after treatment. Up to 80% of breast cancer patients demonstrate a decrease in cognitive capacity, summarized as the symptom-complex “Cancer Related Cognitive Impairment (CRCI)”. In about 35% of affected patients, cognitive symptoms – as e.g. deficits in processing speed, attention, memory and executive functions, persist for months, or even years after completion of medical treatment, impairing daily functioning, limiting ability to return to work and decreasing overall quality of life. Attention to physical activity therefore as a potential supportive care option is increasing. Anyhow, evidence for positive effects of exercise on CRCI is still lacking. Methods: Against this background, the prospective, two-arm, 1:1 randomized, controlled trial aims to investigate the influence of first line chemotherapy accompanied by exercise training on CRCI in 120 patients with breast cancer at the local University Hospital. Besides objective (primary outcome) and subjective cognitive performance, biomarkers and secondary assessments which are suspected to be involved in the pathogenesis of CRCI will be evaluated. The intervention group will perform a defined supervised exercise program (High Intensity Interval Training - HIIT) at least once a week in addition to a heart rate controlled home-based low-intensity endurance and strength training for one year. Spiroergometry will be performed at baseline, after 6 and 12 months to monitor progression of maximal and sub-maximal exercise performance in both groups and to adapt training load in the intervention group. As CRCI is believed to be connected to either functional and/or morphological hippocampal damage due to chemotherapy, head MRIs and hippocampal volume measurements will be performed. Furthermore, a specific neuropsychological test battery for breast cancer patients has been designed in order to detect early signs of cognitive impairments in patients and to be integrated in practice. Discussion: This study clarifies how a long-term supervised exercise intervention program during and after chemotherapy treatment affects CRCI, enables optimization of supportive care and objectifies limits of psychological and physical resilience in breast cancer patients.